Unveiling the Multifaceted Dance of Distractions: Thumbing Through the On-Screen Distractions Throughout Memrise MALL Experience - Abidin, Azwar (REiLA : Journal of Research and Innovation in Language, 2023)
The detrimental impact of screen distractions, including heightened cognitive-emotional engagement and reduced concentration spans, remains to be fully explored. This case study investigates EFL students’ perceptions of screen distractions in mobile-assisted language learning (MALL) and explores their potential implications on learning outcomes. The study employs a descriptive methodology and purposively samples 46 first-year university students who are not majoring in English as participants. During a two-week trial, the participants use the Memrise English learning app to complete Beginner’s levels (A1 and A2). Screen recordings, user account credentials, and interview excerpts are collected from shared Google Drive folders and focus-group sessions. Thematic data analysis is conducted to gain insights into the participants’ perception of screen distractions. Results reveal that social networks and entertainment apps (63.43%) are the primary sources of distraction, followed by web browsing (22.29%), incoming notifications and pop-up messages (11.45%), and incoming calls (2.83%). Participants perceive these distractions as driven by a psychological impulse to avoid missing updates. While the participants demonstrate an impressive aptitude for adapting to and navigating Memrise MALL resources, they lack necessary support to manage distractions, resulting in a failure to meet learning objectives. The study emphasizes the importance of incorporating set times for learning and optimizing screen learning to be distraction-free. Furthermore, it highlights the negative consequences of multitasking and interruptions on students’ MALL performance, underscoring the need for structured use of social media to enhance engagement and academic achievement. Students’ perception of Memrise MALL is generally positive, with reported benefits such as improved recall, concentration, motivation, and engagement. However, distraction management and material connection are essential contributors in successful MALL experience.